REMOTE CONTROL OF MICROCONTROLLER-BASED MANAGEMENT SYSTEM - MOHD.ZAIN, MOHD.ROSEDI (Universiti Teknologi Petronas, 2004)
Remote Control ofMicrocontroller-Based Management System comprises of two main integrated components, Radio Frequency (RF) remote control and microcontroller-based systems. The system manages devices status monitoring and is designed with recovery action on any fault occurrences. The aim of the project is to produce a reliable system that offers easy handling and effective remote control system as one unit of advance management system. The objectives of Remote Control of Microcontroller-Based Management System are to design and construct a microcontroller-based system that effectively monitors devices status; to develop a Radio Frequency (RF) Remote Control System that enables data management through wireless transmission medium; to interface the system with serial communication interface that enables communication between devices and PC and to design system that user-friendly and reliable to real environment. Most of management system is a passive system. This type of system requires manned guarding on site to manage devices of a system. However, in diverse application, the need of more effective system is alarming where assets or security is the major concern. Therefore, the project aims generally to reduce the problem and offer for better enhancement system. This final dissertation presents the development of a management system which is an integration of remote control and microcontroller-based. The system monitors the devices status and alerts the user on the status via Graphical User Interface (GUI). Generally, the system introduced a RF remote control to replace hard-wired system and produce a dynamic data transmission system. It is geared up with a PIC16F84 microcontroller to drive the outputs besides provides communication between devices and PC. Overall, the project is the best platform to improve the traditional management system and ignites another innovative invention in the future.